Septic encephalopathy in the elderly – biomarkers of potential clinical utility - Schütze, Sandra; Drevets, Douglas A.; Tauber, Simone C.; Nau, Roland (Frontiers in Cellular Neuroscience, 2023)
Next to acute sickness behavior, septic encephalopathy is the most frequent involvement of the brain during infection. It is characterized by a cross-talk of pro-inflammatory cells across the blood-brain barrier, by microglial activation and leukocyte migration, but not by the entry of infecting organisms into the brain tissue.Septic encephalopathy is very frequent in older persons because of their limited cognitive reserve. The predominant clinical manifestation is delirium, whereas focal neurological signs and symptoms are absent. Electroencephalography is a very sensitive method to detect functional abnormalities, but these abnormalities are not specific for septic encephalopathy and of limited prognostic value., and rRoutine cerebral imaging by computer tomography usually fails to visualize the subtle abnormalities produced by septic involvement of the brain. Magnetic resonance imaging is by far more sensitive to detect vasogenic edema, diffuse axonal injury or small ischemic lesions.Routine laboratory parameters most suitable to monitor sepsis, but not specific for septic encephalopathy, are C-reactive protein and procalcitonin. The additional measurement of interleukin (IL)-6, IL-8, IL-10 and tumor necrosis factor- increases the accuracy to predict delirium and an unfavorable outcome. The most promising laboratory parameters to quantify neuronal and axonal injury caused by septic encephalopathy are neurofilament light chains (NfL) and S100B protein. In contrast, plasma nNeuron-specific enolase (NSE) plasma concentrationsdid not correlate with outcome in several studies, probably because of the are strongly influenced byof hemolysis on its measurement. We propose to determine NSE only in non-hemolytic plasma or serum samples for the estimation of outcome in septic encephalopathy.